David Hume : Historical Thinker, Historical Writer - Spencer, Mark G. (Book collections on Project MUSE., 2013)
"A transdisciplinary collection of essays focusing on David Hume as historian, and arguing that his "historical" and "philosophical" works are more intimately connected than scholars have often assumed"--